LEGAL FUNDAMENTALS OF WOMEN'S AND GIRLS 'RIGHTS IN UZBEKISTAN - Madumarov Talantbek Tolibjonovich; Turdiyeva Sohibaxon Rasuljon qizi (Scholar Express Journals, 2021)
Therefore, respect for the mother, the woman, her rights, and the protection of her rights and freedoms have not lost their relevance at all times. Equality between women and men means that they have equal rights and responsibilities.
Keywords: Women's and Girl's rights; law; Constitution of the Republic of Uzbekistan; states.